Short Term Inflation Determinants in Barbados - Impavido, Gregorio (Washington, D.C. : International Monetary Fund, 2018)
Inflation in Barbados is mainly imported. But how are external shocks transmitted to the domestic economy? Shouldn't there be also a domestic component, albeit very small, given the presence of capital controls? We focus on short term dynamics and contribute to the existing literature in three ways: (i) we identify the process with which inflation expectations are likely to be formed in Barbados; (ii) we add forward looking inflation expectations as one of the main channels through which external monetary shocks are transmitted to the economy; and (iii) we measure the importance of domestic shocks. We find that due to the peg, forward-looking inflation expectations in the reserve currency country are an important component of the inflation expectation process in Barbados and that they are a key channel in the international monetary transmission mechanism. Domestic factors, mainly monetary shocks, also matter given the limited degree of monetary autonomy provided by capital controls.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet